2019
DOI: 10.1002/ange.201905014
|View full text |Cite
|
Sign up to set email alerts
|

Decorated Traditional Zeolites with Subunits of Metal–Organic Frameworks for CH4/N2 Separation

Abstract: Metal-organic frameworks (MOF) materials are promising materials for gas separation, but their application still faces various challenges.As trategy is nowr eported for introducing subunits of MOFs into traditional zeolite frameworks to obtain applicable adsorbents with advantages of both zeolites and MOFs.The subunits of ZIFs were introduced into zeolite Yand zeolite ZSM-5 for CH 4 /N 2 separation. Both the molecular simulation and experimental results validated that the IAST CH 4 /N 2 selectivity of the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Very recently, Liu and coworkers introduced MOF subunits or fragments into traditional zeolite frameworks including zeolite Y and ZSM-5 to enhance the CH 4 /N 2 separation selectivity of traditional zeolite adsorbents. 141 They found that the CH 4 /N 2 selectivity of the composites according to the ideal adsorbed solution theory improved significantly, much higher than the individual zeolite or ZIF components.…”
Section: Mof Encapsulation To Produce Hierarchical Mof Compositesmentioning
confidence: 99%
“…Very recently, Liu and coworkers introduced MOF subunits or fragments into traditional zeolite frameworks including zeolite Y and ZSM-5 to enhance the CH 4 /N 2 separation selectivity of traditional zeolite adsorbents. 141 They found that the CH 4 /N 2 selectivity of the composites according to the ideal adsorbed solution theory improved significantly, much higher than the individual zeolite or ZIF components.…”
Section: Mof Encapsulation To Produce Hierarchical Mof Compositesmentioning
confidence: 99%
“…The development of high‐performance adsorbents for separation of CH 4 /N 2 mixtures is particularly challenging, owing to the similar kinetic diameters (CH 4 : 3.80 Å and N 2 : 3.64 Å) and comparable polarizability (CH 4 : 26.0 × 10 −25 cm 3 and N 2 : 17.6 × 10 −25 cm 3 ) of the two compounds 13 . Thus, numerous studies have attempted to improve CH 4 /N 2 separation performances using various adsorbents, for example, porous carbons, 14 zeolites, 15 and metal–organic frameworks (MOFs) 16 . For instance, Ma and coworkers prepared a novel MOF—ATC‐Cu (H 2 ATC = 1,3,5,7‐adamantane tetracarboxylic acid)—as a new type of CH 4 nano‐trap that exhibited a benchmark CH 4 capacity of 2.9 mmol/g and CH 4 /N 2 selectivity (50/50, v/v) of 9.7 at 298 K and 1 bar 17 .…”
Section: Introductionmentioning
confidence: 99%
“…One potential strategy for accomplishing this goal involves the selective adsorption of dilute CH 4 from a stream of CH 4 /N 2 by porous materials, which would be both economically and operationally feasible, as well as highly energy efficient. In this regard, many adsorptive materials, including metal–organic frameworks (MOFs), zeolites, and carbon‐based adsorbents, have been examined for the separation of CH 4 /N 2 7‐10 . Specifically, MOFs comprise a new generation of porous materials that have recently demonstrated excellent CH 4 adsorption properties; for example, MOF‐177, 11 M 3 (HCOO) 6 (M = Co, Ni), 12 Co 3 (C 4 O 4 ) 2 (OH) 2 , 13 all exhibit high uptake values for CH 4 , or high CH 4 /N 2 selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, many adsorptive materials, including metal-organic frameworks (MOFs), zeolites, and carbon-based adsorbents, have been examined for the separation of CH 4 /N 2 . [7][8][9][10] Specifically, MOFs comprise a new generation of porous materials that have recently demonstrated excellent CH 4 adsorption properties; for example, MOF-177, 11 M 3 (HCOO) 6 (M = Co, Ni), 12 Co 3 (C 4 O 4 ) 2 (OH) 2 , 13 all exhibit high uptake values for CH 4 , or high CH 4 /N 2 selectivity. However, these materials still face significant challenges before they can be considered for real applications, such as demonstrating long-term stability under exposure to these gas streams, decreasing the cost of manufacturing these materials, and synthesizing a material that exhibits both high CH 4 /N 2 selectivity and high CH 4 capacity.…”
Section: Introductionmentioning
confidence: 99%